2007
DOI: 10.1021/bi602599d
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a Designed Spirocyclic Helical Ligand Binding at a Two-Base Bulge Site in DNA

Abstract: The solution structure of the complex formed between an oligodeoxynucleotide containing a twobase bulge (5′-CCATCGTCTACCTTTGGTAGGATGG) and SCA-α2, a designed spirocyclic helical molecule, has been elucidated. SCA-α2, a close mimic of the metabolite, NCSi-gb, of the DNA bulge-specific enediyne antibiotic neocarzinostatin, differs in possessing a more stable spirocyclic ring system and in lacking certain bulky groupings that compromise bulged DNA binding. This study provides a detailed comparison of the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Considering that these two NCS derivatives have the similar composition and structure, the striking differences observed from their DNA complexes provided important insight into DNA recognition and specificity, which are valuable for drug design and discovery. Later on, the same research group designed a new spirocyclic helical ligand, which is similar to the NCSi‐gb structure without the bulky cyclocrabonate moiety, and they solved the solution structure of a two‐base bulge‐containing DNA bound with this new ligand . However, the structure revealed that this ligand binds to the minor groove.…”
Section: Targeting Dna With Minor and Major Groove Bindersmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that these two NCS derivatives have the similar composition and structure, the striking differences observed from their DNA complexes provided important insight into DNA recognition and specificity, which are valuable for drug design and discovery. Later on, the same research group designed a new spirocyclic helical ligand, which is similar to the NCSi‐gb structure without the bulky cyclocrabonate moiety, and they solved the solution structure of a two‐base bulge‐containing DNA bound with this new ligand . However, the structure revealed that this ligand binds to the minor groove.…”
Section: Targeting Dna With Minor and Major Groove Bindersmentioning
confidence: 99%
“…Goldberg and co‐workers solved a solution structure of a designed spirocyclic helical ligand (SCA‐alpha2) (Fig. A) bound at the two‐base bulge site in a DNA duplex [d(5′‐CCATCGTCTACCTTTGGTAGGATGG‐3′) 2 ] . SCA‐alpha2 is a close mimic of the previously discussed NCSi‐gb binder to the major groove.…”
Section: Targeting Unmatched Bulge Dna Junctions and Phosphate Backmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 This is further supported by comparison of the ORTEP for the basic spirocyclic structure 11 (Figure 3), 14 where the (offset) arenes seem ideally suited to occupy the floor of the bulged cavity, the appended (glycosyl) elements serving to impart secondary, sequence selectivity.…”
Section: Rationalization For Bindingmentioning
confidence: 81%
“…Several groups have shown an interest in developing small molecules that possess specific effects for DNA triplet repeat strand slippage [14][15][16][17][18][19][20][21][22][23]. The most promising and successful bulge-specific agent discovered to date originated from studies on the enediyne natural product neocarzinostatin chromophore (NCS-chrom) [24].…”
mentioning
confidence: 99%